Can Linked Electronic Medical Record and Administrative Data Help Us Identify Those Living with Frailty? - Sabrina Wong; Alan Katz; Tyler Williamson; Alexander Singer; Sandra Peterson; Carole Taylor; Morgan Price; Rita McCracken; Manpreet Thandi (International Journal of Population Data Science, 2020)
Introduction. Frailty is a complex condition that affects many aspects of a patients’ wellbeing and health outcomes.